Preoperative misoprostol in reducing blood loss during myomectomy - Yousry O.S El Maraghy; Khaled M Abdallah; Abdallah A. Moussa (Wolters Kluwer Medknow Publications, 2023)
Background and aim Uterine myomata are by far the most common benign tumors in women of fertility age. Myomectomy can be used to treat manifested uterine myomas while maintaining the ability to become pregnant. The most serious operative risk is uncontrolled intraoperative bleeding with life-threatening complications, making the procedure more dangerous than hysterectomy and necessitating the services of an experienced surgeon. Several ways are being applied to alleviate this complication. The study aim was to evaluate the role of sublingual misoprostol (prostaglandin E1, 400 μg) administered 60 min preoperatively for reducing blood loss during abdominal myomectomy. Patients and methods This randomized prospective controlled study was applied on 40 women with manifested uterine myomas, who were subsumed for myomectomy. Among women subsumed for abdominal myomectomy surgery, 60 min before the surgery women in the study group (n=20) were administered a single dose of sublingual misoprostol (400 μg) while those in the control group (n=20) were administered placebo. Results Postoperative blood loss, postoperative hemoglobin, and hospitalization time mean (252.5±170.5 ml, 10.8±1.02 g/dl, and 1.8±0.4 day, respectively) were significantly reduced (P=0.003, 0.032, and 0.004, respectively) in patients given preoperative sublingual misoprostol, and so there were consequently higher postoperative values of hemoglobin in these patients. As regards the operation time, intraoperative blood loss, and blood transfusion there was a decreased need in the study group but not statistically significant P-value (0.065, 0.077, and 0.311, respectively). Conclusions A single preoperative dose of sublingual misoprostol may be a simple, easily applicable, and cozy method for reducing intraoperative blood loss during abdominal myomectomy.